Relationship of Students' Perceptions on Vocational Education and Career Information on Learning Outcomes Students of Smkn 2 Padang - Ernawaty Ernawaty; Waskito Waskito; Wakhinuddin Simatupang; Hasan Maksum (International Journal of Educational Dynamics, 2021)
From the results of the initial study at SMKN 2 Padang, it turns out that the learning outcomes of students at SMKN 2 Padang are still low. Student learning outcomes are determined by many factors, including students' perceptions of vocational education (internal) and career information (external). This study aims to reveal the relationship between students' perceptions of vocational education and career information on student learning outcomes of SMKN 2 Padang. There are three hypotheses proposed in this study, namely; the relationship between student perceptions of vocational education to student learning outcomes of SMKN 2 Padang, the relationship of career information to student learning outcomes of SMKN 2 Padang, and the relationship between student perceptions of vocational education and information together on student learning outcomes of SMKN 2 Padang. For this study, the population used was 440 people with a sample of 82 students of class XII SMKN 2 Padang who were taken by using a stratified proportional random sampling technique. The instrument used is in the form of a questionnaire with a Linkert scale model which has been tested for validity and reliability in advance. The results of this study reveal that; 1) there is a strong relationship between students' perceptions of vocational education on student learning outcomes of SMKN 2 Padang of 0.598 or 59.8%, 2) there is a strong relationship between career information and student learning outcomes of SMKN 2 Padang of 0.467 or 46.7% and 3) there is a strong relationship between students' perceptions of vocational education and career information together on student learning outcomes of SMKN 2 Padang which is significant at 0.599 or 59.9%. Based on the findings of this study, it can be concluded that students' perceptions of vocational education and career information are two important factors that have a strong relationship with student learning outcomes of SMKN 2 Padang. Therefore, it is suggested to the parties concerned to pay attention to these two factors so that the learning outcomes of students at SMKN 2 Padang can increase.